Implied licences in copyright law - Mysoor, P (2017)
Copyright licences can be implied when the doing of a restricted act is covered neither by the express licence of the copyright owner, nor by one of the statutory limitations and exceptions. The manner in which copyright licences are implied, therefore, holds the key to broadening the scope of permissible acts. In contrast to the rigidity of statutory limitations and exceptions, implied licences are more malleable in being able to respond to a diverse set of circumstances, as the need arises. Thus, implied licences can serve as a flexible and targeted mechanism to balance competing interests, including those of copyright owners and content users, especially in today’s dynamic technological environment. However, implication as a process is contentious, and there are no established rules for implying a licence. Implication of a copyright licence is even more complicated because the conceptualisation of a copyright licence is unsatisfactory. The resulting uncertainty has prevented implied licences from being embraced more readily by the courts. The objective of this thesis is, therefore, firstly, to reconceptualise a copyright licence that is broad enough to accommodate the diverse circumstances in which copyright licences arise, and certain enough to assist in finding their constituents; secondly, to propose frameworks for implying copyright licences in a methodical and transparent manner, based on three sources: the consent of the copyright owner; an established custom; and state intervention to achieve public policy goals. The frameworks are also customised differently for implied bare and implied contractual licences. The thesis demonstrates the robustness of these frameworks by rationalising them with the existing case law. Underscoring the contemporary relevance of implied licences, in conclusion, the thesis tests and validates the frameworks in relation to three essential and ubiquitous functions on the internet – browsing, hyperlinking and indexing.